Relationship between Knowledge and Attitude towards Dengue Fever Prevention - Wiwiet Susan Amelia; Yulis Marita; Adib Kamil Bin Husen (School of Health Sciences Al-Ma'arif, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the Dengue virus and transmitted by the Aedes aegypti mosquito. This disease can attack all ages and can cause death. This research aims to determine the relationship between knowledge, attitudes and the role of jumantik cadres in preventing Dengue Hemorrhagic Fever (DHF) in the work area of the Tanjung Baru Community Health Center UPTD. This research uses a correlational quantitative method with a cross sectional approach and a sample size of 318 people. The variables studied are presented in the form of a frequency distribution table and tested using univariate and bivariate analysis, namely by using demographic data questionnaire instruments, knowledge level questionnaires, education questionnaires and health worker support questionnaires. The research results concluded that the chi square test results showed a value of ρ 0.000, which means there is a significant relationship between knowledge and community attitudes towards dengue prevention efforts.